Insights into the effect of magnetic interactions on the magnetization process of matrices in high gradient magnetic separation. (1st December 2021) - Liu, Jialuo; Wang, Fengyu; Chen, Junming; Xu, Limin; Cao, Quanliang
Highlights: Magnetic interactions between matrix elements in HGMS affect magnetization process. The limitations of conventional magnetization prediction methods are analyzed. A new method for predicting the magnetization process of matrices is proposed. The versatility and accuracy of the method are verified by numerical simulations. Abstract: In-depth understanding and prediction of the magnetization process of matrices in high gradient magnetic separation are essential for matrix design and performance analysis. However, the existing research typically ignores the magnetic interactions between magnetized elements in the matrices. This article numerically reveals the role of the magnetic interactions on the magnetization process of these elements with different configurations, showing that both the gap distance between elements and the relative direction between the applied magnetic field and the matrix structure have a significant effect on the magnetization of elements in matrices. Meanwhile, it is pointed out that the effect of magnetic interactions limits the application of the existing methods for predicting magnetization state of matrices. To solve this problem, a convenient and versatile method is further proposed with considering magnetic interactions and is validated by numerical simulations, providing an effective tool to determine applicable magnetization models of matrices in different situations.